Renewable energy scenarios for sustainable electricity in Malaysia and the application of analytical hierarchy process (AHP) for decision-making - Irina Harun,; Li Yang, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Renewable energy (RE) is an important addition to existing energy systems, indispensable to the sustainable development of human society now and in the future. Renewable energy is advantageous as it is clean, renewable and sustainable. Although the global power supply mainly relies on fossil fuels, as fuels are consumed and the formation cycle is extremely long, resources will gradually decrease and costs will increase accordingly. There are many types of renewable energy, and the selection of which RE should be chosen in a specific situation depends on many factors. The objective of this study is to develop a decision-making framework based on the Analytical Hierarchy Process (AHP) which covers four available renewable energy technologies in Malaysia. Through this process, the most critical issues in implementing the renewable energy systems can and have been identified which includes technology, ecological environment and market issues that must be overcome. The AHP results show that hydropower has great potential for electricity generation in Malaysia, while biomass and wind are ranked second and third respectively, and solar is ranked fourth. Nevertheless, this research had only considered four criteria with limitations in terms of the sub-criteria chosen. The accuracy of this framework may be improved if additional criteria are included and analyzed which can closely simulate the actual scenario of renewable energy development in Malaysia. Hence, through continuous optimization of the energy structure, energy security can be ensured while regional development strategies can be promoted for a balanced development of sustainable energy systems in the region.